The Effectiveness of Talent Management Practices on Organisational Performance in Malaysian SMEs - Ong, Ee Yan (2015)
With the increasing adaptation of evidence based Talent Management practices by large and multinational corporations, Small and Medium sized Enterprises (SMEs) face additional challenges in competing for Talent. It is difficult for SMEs to directly adapt the practices of larger firms and face more risks due to vast differences in internal resources and the more significant impact of labour turnover. However, SMEs form the backbone of the economy in Malaysia and contribute more to national employment than private corporations. Thus, it is of national interest to ensure that SMEs remain productive and highly competitive with effective management of Human Capital and to overcome the stigma of SMEs in Malaysia as unfavourable employment options. The aim of this study is to examine the level of effectiveness of Talent Management Practices on Organisational Performance in Malaysian SMEs. Talent Management Practices encompasses Staffing and Recruitment, Training and Development, Rewards and Recognition and Retaining Practices. Organisational Performance in this study is measured by Job Satisfaction and Organisational Commitment. Primary data was collected from 185 employees of Malaysian SMEs from the service sector with the use of a survey questionnaire and was complimented with a semi-structured interview with 7 Human Resource Managers/Administrators. The effective Talent Management factors include accurate job descriptions, clear company purpose and direction, opportunities for new experiences, clear and attainable pathway, honest, fair and clear appraisals, financial rewards, open and honest communication, demonstration of leadership by management, autonomy, flexibility, encouraging employee feedback, and a respectful culture and work environment. This study found that Staffing and Recruitment, Training and Development, Rewards and Recognition and Retaining Practices were effective towards Organisational Performance of Malaysian SMEs. However, there appears to be a gap between the expectations of effective Talent Management practices of employees and the expectations of their employers with the practices currently employed. Thus, the recommendations for managers of Malaysian SMEs to better manage talent to drive Organisational Performance include forming partnership with education institutes, adequately defining competencies, offering cafeteria benefits, external benchmarking, and using company online forums. The recommendation for the Malaysian government’s SME agency is to enhance the credibility of the training provided to improve the effectiveness and utilisation of their training budget.